Influence of Central Sensitisation on Posture, Stability, and Walking Among Individuals with Non-Specific Chronic Low Back Pain (International Journal of Physiotherapy, 2025)
Background: Non-specific chronic low back pain (NSCLBP) is a prevalent musculoskeletal condition often associated with central sensitisation, which amplifies pain perception and disrupts sensory processing, motor control, and postural regulation. This study investigated the association between central sensitisation and changes in postural stability, spinal posture, and gait in individuals with non-specific chronic low back pain (NSCLBP).Methodology: A cross-sectional observational study was conducted at the Nitte Institute of Physiotherapy, Mangaluru, involving 87 young adults (18–25 years), comprising 35 males and 52 females, with NSCLBP. Participants were assessed using the Central Sensitisation Inventory (CSI), the Multi-Directional Reach Test (MDRT) for postural stability, the flexi-curve technique for spinal posture, the PALM meter for pelvic alignment, and 2D gait analysis for cadence, step length, and speed. Statistical analyses included one-way ANOVA, Tukey post hoc tests, and Pearson correlation.Results: Higher Central sensitisation scores were associated with reduced postural stability, particularly in backwards and lateral directions (p < 0.05). Gait analysis revealed the differences in cadence (p = 0.026) and in step length (p = 0.037) among central sensitisation groups. Spinal mobility was inversely correlated with central sensitisation scores (r = -0.187, p = 0.046), and greater pelvic asymmetry was observed in participants with elevated central sensitisation. Correlation analysis confirmed that central sensitisation was significantly related to impaired postural control, altered gait, and disrupted body alignment.Conclusion: Central sensitisation significantly impacts postural stability, spinal alignment, and gait in individuals with NSCLBP, highlighting the need for targeted rehabilitation strategies.Trial Registration: CTRI/2024/06/068697